Field Investigation of Wave Attenuation in a Mangrove Forest Dominated by Avicennia marina (Forsk.) Viern. - Xing Wei; Wenyuan Mo; Lanlan Xiong; Xin Hu; Hao Cheng (Plants)
Based on field observation at the north coast of the Zhanjiang Bay in southern China, the characteristics of wave attenuation due to the drag force of one mangrove species, Avicennia marina (Forsk.) Viern., were quantitatively analyzed. The results demonstrated that the mean significant wave height decreased by ~62% within a forest belt up to 80 m due to various bio-physical interactions. Affected by the unique vertical configuration of vegetation, the wave attenuation rate is positively correlated with water depth. The drag force within the forest can be approximated by the function <semantics>Cd=0.7344e0.1409Am</semantics>, where Am is the projected area of the submerged obstacle at a certain water depth. The wave attenuation rate and the vegetation density (ρveg) in volume (‰) satisfy the fitting relationship of <semantics>r=5×10−4·ρveg−3.6×10−3</semantics>. These findings can accumulate quantitative information for studying the influence of mangrove vegetation on wave attenuation characteristics and provide necessary basic data for modeling studies to investigate the processes contributing to the attenuation capacity of mangroves.